EXPERIENCE, KNOWLEDGE, ON FINANCIAL BEHAVIOR, MEDIATION OF LOC, MODERATION OF NUMBER OF DEPENDENTS - Kiki Marti Diana; Lutfi (Jurnal Riset Bisnis dan Manajemen, 2021)
Previous research gave different results regarding financial management behavior and appear research gap, so the researchers aimed to examine whether financial experience and knowledge have a positive effect on financial management behavior, locus of control mediates the effect of financial experience and knowledge on financial management behavior, and the number of dependents moderate effect of financial knowledge on financial management behavior. The sampling technique used purposive sampling, while analysis technique used the Structural Equation Model. Financial experience and knowledge have significant positive effect on financial management behavior. Locus of control mediates effect of financial experience on financial management behavior but is better directly. Locus of control doesn’t mediate effect of financial knowledge significantly on financial management behavior. The numbers of dependents doesn’t moderate effect of financial knowledge on financial management behavior. Otoritas Jasa Keuangan and Surabaya government provide access and education such as seminars, workshops (pension funds, insurance, and investment).